Antagonistic regulation of spermatogonial differentiation in zebrafish (Danio rerio) by Igf3 and Amh - Morais, R. D. V. S.; Crespo, D.; Nobrega, R. H. [UNESP]; Lemos, M. S.; van de Kant, H. J. G.; Franca, L. R. de; Male, R.; Bogerd, J.; Schulz, R. W. (Elsevier B.V., 2017)
Fsh-mediated regulation of zebrafish spermatogenesis includes modulating the expression of testicular growth factors. Here, we study if and how two Sertoli cell-derived Fsh-responsive growth factors, anti-Mullerian hormone (Amh; inhibiting steroidogenesis and germ cell differentiation) and insulin-like growth factor 3 (Igf3; stimulating germ cell differentiation), cooperate in regulating spermatogonial development. In dose response and time course experiments with primary testis tissue cultures, Fsh up regulated igf3 transcript levels and down-regulated amh transcript levels; igf3 transcript levels were more rapidly up-regulated and responded to lower Fsh concentrations than were required to decrease amh mRNA levels. Quantification of immunoreactive Amh and Igf3 on testis sections showed that Fsh increased slightly Igf3 staining but decreased clearly Amh staining. Studying the direct interaction of the two growth factors showed that Amh compromised Igf3-stimulated proliferation of type A (both undifferentiated [A(und)] and differentiating [A(diff)]) spermatogonia. Also the proliferation of those Sertoli cells associated with Aund spermatogonia was reduced by Amh. To gain more insight into how Amh inhibits germ cell development, we examined Amh-induced changes in testicular gene expression by RNA sequencing. The majority (69%) of the differentially expressed genes was down-regulated by Amh, including several stimulators of spermatogenesis, such as igf3 and steroidogenesis-related genes. At the same time, Amh increased the expression of inhibitory signals, such as inha and id3, or facilitated prostaglandin E-2 (PGE(2)) signaling. Evaluating one of the potentially inhibitory signals, we indeed found in tissue culture experiments that PGE(2) promoted the accumulation of Aund at the expense of Ada and B spermatogonia. Our data suggest that an important aspect of Fsh bioactivity in stimulating spermatogenesis is implemented by restricting the different inhibitory effects of Amh and by counterbalancing them with stimulatory signals, such as Igf3. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Follicle-stimulating hormone; Insulin-like growth factor; Anti-mullerian hormone; RNA sequencing; Testis; Spermatogenesis